(untitled) (Scientific journal of the Fergana State University, 2024)
The article analyzes the language of motorsport and its main lexical and stylistic manifestations. The article analyzes all elements and areas that directly or indirectly make up the vocabulary of this area. The purpose of the article is to analyze motorsport language and find an answer to the question of whether it can be considered as a separate category of professional language. In the work, the language of motorsport is analyzed from the point of view of considering motorsport as an institutional sphere. The main attention is paid to two main components - technical and terminological aspects. The article also examines such components as the language of the media and the language of fans, which are also a source of replenishing the specifics of the language of motorsport with new concepts. As a result of the study, it was concluded that studying the language of motorsport as a separate professional field requires analysis of not only terminology, but also other related fields, including sports jargon and the language of journalism.